History and Politics of Attacks on Shrines in Pakistan - Wajid, Abdul (Al-Amīr Research Journal for Islamic Studies, 2024)
The nature and dimension of ideological conflicts in the world has dramatically changed with the inception of 21st century. In Pakistan, the war on terror against Al-Qaida and Taliban in Afghanistan has fueled the existing theological differences among the various religious groups and paved the way for intra sectarian violence and militancy in Pakistan. To counter violence and militant attitudes, state at first patronized the mystical version of Islam for social cohesion. Secondly state used force against the united militant front in the shape of Tehreek Taliban Pakistan (TTP) to maintain political order. As a result, a series of attacks on shrines started across Pakistan. This research tries to find out that on what basis the militant outfits across Pakistan managed to transform themselves into a single organization and what are the political motivations and religious zealousness which provoked them to attack and destroy the important shrines in Pakistan? In answering the critical question, the present study uses the key concept of Ibn Khaldun that is asabiyah, as expressed in his book Muqaddimah and links the concept of asabiyah with intra sectarian conflict in the shape of attacks on shrines in Pakistan. The absence of conceptual historical framework left a wide gap to analyze and theorize not only the past trends but also the emerging trends of present ideological collisions within Islam. These trends have drastic implications on politics as well as social fabrics of the country. Therefore, the present study evaluates and examines the problem on the basis of Ibn Khaldun’s concept of asabiyah and its relation with political power. Key Words: Asabiyah, War on Terror, Shrines, Lal Masjid, TTP, Al-Qaida